Co głosi relatywizm poznawczy? Rekonstrukcja konstytutywnych twierdzeń relatywizmu - Leszczyńska, Dorota (Filozofia Nauki, 2005)
The aim of the paper is to present a reconstruction of the constitutive theses of cognitive relativism. The reconstruction is based on some examples of well-known theses and statements that are conceived to be relativistic. I distinguish three constituents of cognitive relativism: 1) the thesis of constructive character of cognition, 2) the thesis of pluralism of cognitive schemes, 3) the thesis of incommensurability of cognitive schemes. The rest of the article aims at, first, proving that Quine's philosophical standpoint is not relativistic as it clashes with the third thesis of relativism. And, second, I try to argue that a relativist may avoid the consequence of agnosticism but, which is not surprising, he/she has to radically reject the idea of the objective truth as the purpose of our cognition.